2009
DOI: 10.1073/pnas.0902322106
|View full text |Cite
|
Sign up to set email alerts
|

Large spinose microfossils in Ediacaran rocks as resting stages of early animals

Abstract: Large (>100 m), profusely ornamented microfossils comprise a distinctive paleontological component of sedimentary rocks deposited during the Ediacaran Period (635-542 million years ago). Smaller spinose fossils in Paleozoic rocks have commonly been interpreted as algal cysts or phycomata, but the Ediacaran populations differ from modern algal analogs in size, shape, ultrastructure, and internal contents. In contrast, cysts formed during the diapause egg-resting stages of many metazoans share features of size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 77 publications
0
105
0
Order By: Relevance
“…Proterozoic marine environments would have been characterized by O 2 levels that departed strongly from background mean pO 2 , and the oxygen demand and marine habitat of different life history stages could present physiological bottlenecks that are currently poorly known for basal metazoan organisms. Indeed, microfossil evidence for metazoan life stages adapted for large-scale dispersal across inhospitable environments may represent a paleontological signal for such ecosystem oxygen stress during the Late Proterozoic (24). In this light, our results strongly suggest that the distribution of O 2 within the ocean−atmosphere system played a significant role in structuring evolutionary innovation and ecological success among early animals.…”
Section: Discussionmentioning
confidence: 62%
“…Proterozoic marine environments would have been characterized by O 2 levels that departed strongly from background mean pO 2 , and the oxygen demand and marine habitat of different life history stages could present physiological bottlenecks that are currently poorly known for basal metazoan organisms. Indeed, microfossil evidence for metazoan life stages adapted for large-scale dispersal across inhospitable environments may represent a paleontological signal for such ecosystem oxygen stress during the Late Proterozoic (24). In this light, our results strongly suggest that the distribution of O 2 within the ocean−atmosphere system played a significant role in structuring evolutionary innovation and ecological success among early animals.…”
Section: Discussionmentioning
confidence: 62%
“…Ediacaran acanthomorphs have long been regarded as the resting cysts of various unicellular phytoplanktonic algae [41]. However, recent studies have shown that they may have more diverse affinities, and some of them may be animal resting cysts [6,42].…”
Section: Anoxia and The Decline Of Doushantuo Acanthomorphsmentioning
confidence: 99%
“…Cohen et al [6] interpreted the large Ediacaran acanthomprphs as animal resting cysts, and proposed that their evolutionary rise in the early Ediacaran Period was an ecological response to bottom water anoxia, and their disappearance in the late Ediacaran Period was due to the pervasive oxygenation of continental shelves. Whether Ediacaran acanthomorphs are dormant cysts of protists or animals, it is clear that they must have spent at least part of their life cycle resting in the benthic realm [43].…”
Section: Anoxia and The Decline Of Doushantuo Acanthomorphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a large number of animal embryo fossils have also been found in the lower Doushantuo Formation (~632 Ma) in the Yangtze Gorges area [82,83]. It has been argued that some large acanthomorphic acritarchs from Ediacaran successions in Australia, Eastern European Platform, and Siberia may represent diapause eggs of early animals as well [84]. Because a complete ontogenetic sequence of the Weng'an embryo fossils is still a matter of debate [30,85], alternative interpretations-including green algae, giant sulfur bacteria, and mesomycetozoan-like protists-have been proposed to account for the morphologies of the Weng'an fossils [30,[86][87][88], but so far animal embryos remain the most plausible interpretation for these fossils [28,31,82,89].…”
Section: Previous Knowledgementioning
confidence: 99%